IMPLEMENTASI NILAI-NILAI PANCASILA DALAM MENUMBUHKAN KARAKTER RELIGIUS SISWA KELAS IV DI SDN 001 SANGATTA UTARA KAB.KUTAI TIMUR - Azamul Fadhly Noor Muhammad; Ari Wibowo; Fitri Nur Jannah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Developing religious character forms the character and civilization of a dignified nation and to enlighten the life of the nation, it is necessary to instill the values ​​of Pancasila which aims to develop the potential of students to become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. The purpose of this study is to find out how the instillation of Pancasila values ​​​​is carried out by teachers in fostering the religious character of grade IV students at SDN 001 Sangatta Utara, and to find out what obstacles teachers face in instilling Pancasila values ​​​​in fostering religious character. The application of Pancasila values ​​​​needs to start from the home, school, and community environment. Therefore, the importance of applying Pancasila values ​​​​as a benchmark for achieving values, ethics, morals and attitudes in daily behavior. Thus, with the implementation of Pancasila values, it is hoped that students can apply and implement them in the learning process, such as by doing simple things like praying before starting lessons, obeying school rules and regulations, maintaining harmony with friends by prioritizing tolerance, being active and participatory in discussions to express opinions, and behaving fairly without discrimination. While upholding the motto "Bhinneka Tunggal Ika" (Unity in Diversity). Likewise, the application of Pancasila's core values ​​in Civics (PPKn) subjects in educational institutions requires coordination between educators and students to achieve a learning process that aligns with Pancasila values.